Pengaruh variasi komposisi arang kelapa dan kayu berpenguat serat ijuk terhadap sifat fisik dan mekanik komposit kampas rem - Salman, S.; Triady, A.A.A.; Rahman, M.A. (Universitas Mataram, 2018)
The breaking system is a mechanical system to reduce the movement of the wheels. The existing nowadays friction material from asbestos belongs to cancer risk besides accelerating the damage of the brake drum. Therefore, the green friction material needs to be developed.The objective of this study is to determine the best composition of coconut shell of charcoal powder, wood powder, palm fibre and phenol resin as an alternative substitution of brake friction material. Variations in the percentage composition of coconut shell of charcoal powder were 45%, 40%, 35%, 30% and 25%. Sawdust and phenol resin were constant at 20% and 25% respectively, while the palm fibres were 10%, 15%, 20%, 25% and 30%. The specimens were produced by moulding under pressure 4 tons and heated at temperature 150o for 3 hours. The tests were wear, hardness, tensile test and micro photograph.The results showed that the lowest wear value is 1,68x10-6 gr/mm2.s and the highest one is 3,71x10-6 gr/mm2.s. The highest hardness value is 60,497 HBN and the lowest one is 54,329 HBN. While the maximum tensile stress is obtained at 9,50x10-1 MPa and the lowest one is 2,01x10-1 MPa. The best composition is obtained at the composition of 45% of coconut shell of charcoal powder, 20% of wood powder, 10% of palm fibre and 25% of resin phenol.